Effect of Si infiltration method on the properties of biomorphous SiC - Kiselov, V.S.; Kalabukhova, E.N.; Sitnikov, A.A.; Lytvyn, P.M.; Poludin, V.I.; Yukhymchuk, V.O.; Belyaev, A.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Two types of wood-based biomorphous SiC composites with different microstructure were obtained by infiltration of carbon template with liquid or vapour silicon. The oak, pine, lilac, walnut, acacia woods available in Ukraine were used as the biological template in this work. SEM, optical and AFM data indicated that biomorphous SiC obtained by melt infiltration consists of crystalline phase of 3C-SiC, while that of vapor infiltration results in formation of crystalline and amorphous phases of 3C-SiC. The same results were obtained for infiltration of carbon fibers. Thus, it was suggested that the mechanism of SiC formation is governed by the infiltration method.